(untitled) (Journal of the College of Basic Education, 2022)
In countries such as Iraq where English is taught as a foreign language, it is common to notice that in spite of teaching English for twelve years, most students are unable to speak in a proper way. This fact has been documented by several studies on speaking ability in Iraq. Therefore, the researcher highlighted this issue as an attempt to recover it through using new two techniques which are Three-Step Interview and Talking Chips. The population of the present study is made up of fourth preparatory male students in Baghdad Governorate, the third Directorate General of Education in Al-Rusafa Third. The sample of the study, which is chosen randomly, consists of two sections of the fourth preparatory male students, scientific branch, at Al-Shaheed Qassim Al-Mubarqa’ Preparatory School. The total number of the sample was 82. Three-Step Interview was applied on the first section, while Talking Chips was applied on the second one. The experimental design of this study is the pre-test post-test non - equivalent groups. The experiment lasted two months and a half during the academic year 2016-2017. It started on the sixth of March and ended on the eleventh of May. The researcher himself taught all the two groups. Both of the pretest and the posttest are constructed by the researcher and exposed to a jury of experts to verify its validity.